Cognitive Learning Theory: Skill Acquisition and Conditional Knowledge - Clarisa Aprilia (Psikologiya Journal, 2024)
Active learning that focuses on developing students' mental abilities has taken center stage in modern education. Cognitive strategies are key in helping students connect new information with existing knowledge, improve their retention capacity and memory. The thinking approach to learning not only encourages the development of students' cognition but also prepares them to use the brain more effectively in dealing with various situations. Cognitive learning theory emphasizes that a person's behavior is influenced by the perception and understanding of situations related to learning objectives. The focus on the process of learning, not just the outcome, is the cornerstone of this theory. Figures such as Gestalt and Kurt Lewin emphasize the overall organization of information in an individual's understanding. Meanwhile, theories from Jean Piaget and Jerome S. Bruner highlight the child's active role in learning, with an emphasis on discovering and organizing learning materials. The application of cognitive learning strategies has a significant impact on students' problem-solving abilities, strengthening conceptual understanding and developing creative skills. Through this approach, students can internalize their knowledge in everyday life, apply it in relevant contexts, and develop important adaptive skills. The research used a qualitative approach with a focus on case studies and narrative analysis, exploring the influence of cognitive learning strategies on students' ability to solve problems and internalize knowledge.